2000
DOI: 10.1017/s0007114500000623
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of energy and macronutrient intake and related substrate oxidation rates in a buffet-type meal

Abstract: The aim of this present study was to determine the reliability of a buffet-type meal as a measure of spontaneous energy and macronutrient intake. In addition, we evaluated the short-term effects of diet on the composition of the substrate mix oxidized postprandially. Fourteen male subjects had ad libitum access to a variety of foods from a buffet-type meal offered in the laboratory during two identical sessions. The foods comprising the test meal had varying amounts of protein, lipid and carbohydrate. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 23 publications
6
51
2
2
Order By: Relevance
“…VAS measurements in our laboratory have been shown to be highly reliable both before and in response to a meal (Arvaniti et al 2000).…”
Section: Methodsmentioning
confidence: 93%
“…VAS measurements in our laboratory have been shown to be highly reliable both before and in response to a meal (Arvaniti et al 2000).…”
Section: Methodsmentioning
confidence: 93%
“…The randomization with counterbalancing was successful as 3 males (50%) received MPH first and 3 (50%) received placebo first, and 3 females (50%) received MPH first, while 3 (50%) received placebo first, thus controlling for order effects on energy intake. At 11:15 a.m., approximately one hour following the administration of drug or placebo, total food intake and macronutrient preference were assessed by evaluating energy intake from a standardized mixed meal buffet-style eating methodology (Arvaniti et al 2000), with hunger (and other appetite sensations) re-evaluated every 30 min for three hours following completion of the meal to assess satiety. To further evaluate gender differences in satiety from MPH vs. placebo, we calculated satiety quotients for all appetite sensations measured by the VAS (mm/kcal) at 60 and 120 min after the buffet meal, based on the formula reported by Gilbert et al (2009).…”
Section: Design and Experimental Proceduresmentioning
confidence: 99%
“…On the basis of our research experience, it is plausible that VAS were used in this study under conditions that did not really permit an adequate discrimination by this type of tool [12]. Indeed, even if we demonstrated that the use of VAS provides reproducible results [18], we have only been able to document a clinical discrimination with VAS in the context of intervention where body weight loss was substantial [24, 25]. Beyond technical considerations, we cannot exclude the possibility that acute changes in energy intake following exercise and mental work can occur without concordant changes in hunger and other appetite sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Desire to eat, hunger, fullness, prospective food consumption, and desire to eat salty, sweet, or fatty foods were rated on 150 mm VAS. Methods regarding VAS measurement have been previously described by Doucet et al [17], and VAS measurements have been recognized for being highly reproducible [18]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation